2021
DOI: 10.1021/acs.energyfuels.0c03978
|View full text |Cite
|
Sign up to set email alerts
|

Shale Oil Potential and Mobility of Low-Maturity Lacustrine Shales: Implications from NMR Analysis in the Bohai Bay Basin

Abstract: A vital factor influencing shale oil exploration in lacustrine shale reservoirs is oil mobility, which is closely associated with the shale pore structure and fluid properties, especially for the low-maturity lacustrine shales in China. In this study, the oil mobility and shale oil potential in the Middle Eocene Shahejie Formation lacustrine shales (MES shales) of the Nanpu Sag in the Bohai Bay Basin are evaluated by using nuclear magnetic resonance (NMR) experiments. The low-maturity MES shales have low poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Therefore, it can be qualitatively considered that adsorbed water is primarily distributed in small pores and free water is distributed in large pores. Using the relationship of d = F ρ T 2 , the T 2 value can be converted to the pore size ( d , in nanometers) after determining the ρ value. , In this study, the F value was given to be 4. It was found that the pore size controls the microdistributions of adsorbed and free water (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be qualitatively considered that adsorbed water is primarily distributed in small pores and free water is distributed in large pores. Using the relationship of d = F ρ T 2 , the T 2 value can be converted to the pore size ( d , in nanometers) after determining the ρ value. , In this study, the F value was given to be 4. It was found that the pore size controls the microdistributions of adsorbed and free water (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, there is a corresponding relationship between the T 2 value and pore size, and the larger the T 2 value, the larger the pore size will be. 55 Therefore, it can be qualitatively considered that adsorbed water is primarily distributed in small pores and free water is distributed in large pores. Using the relationship of d = FρT 2 , the T 2 value can be converted to the pore size (d, in nanometers) after determining the ρ value.…”
Section: Surface Relaxation Ratementioning
confidence: 99%
“…For Da’anzhai shale, D 1 is the fractal dimension of small pores, with values ranging from 0.6595 to 0.9372, while D 2 represents the fractal dimension of large pores and microfractures, with values ranging from 2.8859 to 2.9563. In addition to pore structure parameters, pore fractal characteristics and fractal dimension can quantitatively characterize pore complexity and heterogeneity (Chen et al, 2021a), D 2 is significantly higher than D 1 , reflecting that the complex macropore–macropore and pore-fracture configuration relationship may promote the flow of shale oil (Chen et al, 2021a), which further supporting that the configuration of OM-related fractures and brittle mineral-related fractures may be the dominant channels for shale oil flow (Figure 3(l)).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the TOC content, shales can be divided into three groups, namely, organic-rich (TOC content ≥1.5%), organic-containing (TOC content ranges 1~1.5%), and organic-poor shale (TOC content ranges 0~1%) (Zhang et al, 2018b;Zhang et al, 2020c;Xiao et al, 2020;Guo et al, 2021;Shan et al, 2021). In terms of mineral contituents, shales can be classified into four types: calcareous (carbonate minerals ≥50%), grapholith (clay minerals ≥50%), siliceous (siliceous minerals ≥50%), and mixed shale (each mineral accounts for less than 50%) (Li et al, 2019;Huang H. et al, 2020;Xia et al, 2020;Chen et al, 2021). Combining the two classification standards, we can achieve three times four, that is, twelve lithofacies types based on the TOC content and mineral constituents, as shown in Tables 3, 4.…”
Section: Lithofacies Typesmentioning
confidence: 99%